Identification of histaminergic neurons through histamine 3 receptor-mediated autoinhibition. (July 2016) - De Luca, Roberto; Suvorava, Tatsiana; Yang, Danqing; Baumgärtel, Wilhelm; Kojda, Georg; Haas, Helmut L.; Sergeeva, Olga A.
Abstract: Using a reporter mouse model with expression of the tomato fluorescent protein under the dopamine transporter promoter (Tmt-DAT) we discovered a new group of neurons in the histaminergic tuberomamillary nucleus (TMN), which, in contrast to tuberoinfundibular dopaminergic neurons of the dorsomedial arcuate nucleus, do not express tyrosine hydroxylase but can synthesize and store dopamine. Tmt-DAT neurons located within TMN share electrophysiological properties with histaminergic neurons: spontaneous firing at a membrane potential around −50 mV and presence of hyperpolarization-activated cyclic nucleotide-gated ion channels. Histamine (30 μM) depolarizes and excites Tmt-DAT neurons through H1 R activation but inhibits histaminergic neurons through H3 R activation thus allowing a pharmacological identification of the different neurons. Single-cell RT-PCR revealed that all histaminergic neurons expressing histidine decarboxylase (HDC) also express H3 R. This includes neurons retrogradely traced from the striatum whose inhibition by a selective H3 R agonist was indistinguishable from the whole population. Prolonged depolarization reduces the autoinhibition. The potency of histamine at H3 R depends on membrane potential and on extracellular and intracellular calcium. Autoinhibition can be impaired by preincubation with capsaicin, a ligand of the calcium-permeable TRPV1 channel or by blockade of Ca 2+ -ATPase with thapsigargin. The pharmacology of autoinhibition is revisited and physiological conditions for its functionality are determined. Usage of reporter mouse models for the safe identification of aminergic neurons under pathophysiological conditions is recommended. This article is part of the Special Issue entitled 'Histamine Receptors'. Highlights: Autoinhibition through H3 R is a reliable identification criterion for histaminergic neurons of the tuberomamillary nucleus irrespective of their axonal projection. Autoinhibition is calcium-sensitive and can be reduced by depolarization or preincubation with the TRPV1 agonist capsaicin. The TMN contains non-histaminergic neurons expressing the dopamine transporter which are excited by histamine through H1 R activation.